COMT Diplotype Amplifies Effect of Stress on Risk of Temporomandibular Pain. (September 2015) - Slade, G.D.; Sanders, A.E.; Ohrbach, R.; Bair, E.; Maixner, W.; Greenspan, J.D.; Fillingim, R.B.; Smith, S.; Diatchenko, L.
When measured once, psychological stress predicts development of painful temporomandibular disorder (TMD). However, a single measurement fails to characterize the dynamic nature of stress over time. Moreover, effects of stress on pain likely vary according to biological susceptibility. We hypothesized that temporal escalation in stress exacerbates risk for TMD, and the effect is amplified by allelic variants in a gene, catechol- O -methyltransferase (COMT), regulating catechol neurotransmitter catabolism. We used data from the Orofacial Pain: Prospective Evaluation and Risk Assessment prospective cohort study of 2, 707 community-dwelling adults with no lifetime history of TMD on enrollment. At baseline and quarterly periods thereafter, the Perceived Stress Scale (PSS) measured psychological stress. Genotyped DNA from blood samples determined COMT diplotypes. During follow-up of 0.25 to 5.2 y, 248 adults developed examiner-verified incident TMD. PSS scores at baseline were 20% greater ( P < 0.001) in adults who developed incident TMD compared with TMD-free controls. Baseline PSS scores increased by 9% ( P = 0.003) during follow-up in cases but remained stable in controls. This stress escalation was limited to incident cases with COMT diplotypes coding for low-activity COMT, signifying impaired catabolism of catecholamines. Cox regression models confirmed significant effects on TMD hazard of both baseline PSS ( P < 0.001), modeled as a time-constant covariate, and change in PSS ( P < 0.001), modeled as a time-varying covariate. Furthermore, a significant ( P = 0.04) interaction of COMT diplotype and time-varying stress showed that a postbaseline increase of 1.0 standard deviation in PSS more than doubled risk of TMD incidence in subjects with low-activity COMT diplotypes (hazard ratio = 2.35; 95% confidence limits: 1.66, 3.32), an effect not found in subjects with high-activity COMT diplotypes (hazard ratio = 1.42; 95% confidence limits: 0.96, 2.09). Findings provide novel insights into dynamic effects of psychological stress on TMD pain, highlighting that effects are most pronounced in individuals whose genetic susceptibility increases responsiveness to catecholamine neurotransmitters.